1979
DOI: 10.1111/j.1399-6576.1979.tb01447.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of General Anaesthesia on Portal Pressure in Liver Cirrhosis and Portal Hypertension

Abstract: In 19 patients with cirrhosis of the liver and portal hypertension, a catheter was inserted into the portal vein using a percutaneous transhepatic technique. The portal pressure was measured during general anaesthesia with and without halothane, and in the awake state. Addition of halothane to the N2O:O2 anaesthesia did not change portal venous pressure, in spite of a significant fall in arterial blood pressure. Portal venous pressure under general anaesthesia with complete muscle relaxation did not differ fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1992
1992

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…This assertion is based on the previously reported relationship between the decrease in cardiac output induced by propranolol and the reduction in portal venous pressure in patients with cirrhosis [6]. In a small group of patients with cirrhosis [1], no significant change in portal venous pressure, measured directly by the transhepatic technique, was noted during general anaesthesia partly induced by halothane. However, previous inves tigations demonstrated that cardiac output decreases in a linear fashion with increasing concentrations halothane [5] and, in this patient series, halothane inhalation might have been insufficient to obtain a sustained decrease in cardiac output and, therefore, in portal venous pressure.…”
Section: Discussionmentioning
confidence: 95%
“…This assertion is based on the previously reported relationship between the decrease in cardiac output induced by propranolol and the reduction in portal venous pressure in patients with cirrhosis [6]. In a small group of patients with cirrhosis [1], no significant change in portal venous pressure, measured directly by the transhepatic technique, was noted during general anaesthesia partly induced by halothane. However, previous inves tigations demonstrated that cardiac output decreases in a linear fashion with increasing concentrations halothane [5] and, in this patient series, halothane inhalation might have been insufficient to obtain a sustained decrease in cardiac output and, therefore, in portal venous pressure.…”
Section: Discussionmentioning
confidence: 95%